Returning to learning: the importance of creating compassionate and collaborative spaces for students re-entering education - Helen Briscoe (Journal of Learning Development in Higher Education)
This case study focuses on the importance of creating compassionate and collaborative spaces for students re-entering education. It highlights the growing body of mature and non-traditional learners in UK higher education institutions and addresses how these students are recruited to universities and supported after enrolment. Key concerns about the expectations and assumptions of these students’ prior abilities, and the importance of offering a safe space to rekindle a joy of learning, are also discussed. The case study focuses on the Returning to Learning initiative in a North-West university which actively engages returning learners by inviting them to be part of an informal community of positive support. Reflections on the process of designing, delivering and assessing the value of this learning community will also be shared, alongside suggestions for a more formal evaluation of the impact of this initiative.